A “three delays” model for severe sepsis in resource-limited countries - Papali, Alfred; McCurdy, Michael T.; Calvello, Emilie J.B. (Journal of critical care, 2015)
The developing world carries the greatest burden of sepsis-related mortality, but success in managing severe sepsis in resource-limited countries (RLCs) remains challenging. A “three delays” model has been developed to describe factors influencing perinatal mortality in developing nations. This model has been validated across different World Health Organization regions and has provided the framework for policymakers to plan targeted interventions. Here, we propose a three delays model for severe sepsis in RLCs. A literature review was performed using the PubMed, Google Scholar, and Ovid databases. Additional sources were found after review of the reference lists from retrieved articles. We propose a three delays model for severe sepsis in adults in RLCs. The model highlights limitations in the 3 basic pillars of sepsis management: (1) sepsis recognition and diagnosis at the time of triage, (2) initial focused resuscitation, and (3) postresuscitation clinical monitoring and reassessment. Characterizing the major barriers to effective treatment of severe sepsis in RLCs frames the problem in a language common to global health circles, which may stimulate further research, streamline treatment, and reduce sepsis-related mortality in the developing world.